Penggunaan Gadget HUBUNGAN LAMA PENGGUNAAN GADGET TERHADAP INTERAKSI SOSIAL PADA ANAK USIA DINI DI PAUD MUTIARA KECAMATAN KUTA SELATAN KABUPATEN BADUNG - Febriani, Shierly Andrianita; Mastryagung, G.A Dwina; Kurnia, Ni Putu Riza (JURNAL MEDIKA USADA, 2024)
Background. Providing gadgets for an extended period is one of the inappropriate stimulation for early childhood. Children who are already addicted to gadgets will have social-emotional development problems. Children who use gadgets will become an antisocial-individuals; therefore, they often ignore and interact less with their surroundings. The purpose of this study was to determine the correlation between the duration of gadget use and social interaction among children at Mutiara Pre-Primary School in South Kuta, Badung Regency. Method. This study employed a correlation analytic research design with a cross-sectional approach. The research sample was 109 respondents recruited through the total sampling technique according to the inclusion and exclusion criteria. Results. Findings indicated that most children used gadgets for a long duration with 70 respondents (64.2%), and almost all children had good social interaction with 107 respondents (98.2%). The results of statistical tests using Chi-Square showed no correlation between the duration of using gadgets and social interaction in early childhood, with a p-value of 0.056 > 0.05. Conclusion. There is no correlation between gadget use duration and early childhood social interaction.